Challenges of International Career for Teachers - Bünyamin Çelik (International Journal of Social Sciences & Educational Studies, 2017)
People for different reasons need to travel abroad. They even travel to another country to work. However, people might experience culture schock due to new values and opinions they encounter in the new culture. It is not always easy to adapt a new environment for some people. Teachers, similarly might have the same problems once they enter in a new culture. Although teachers work abroad to develop their teaching experiences, different cultural values and a new education system they are exposed to in the new country might cause them some social problems. This paper focuses on what kind of problems those teachers who would like to work abroad encounter.